الديمقراطية التشاركية والتنمية المحلية بمنطقةطاسيلي ناجر دراسة حالة برنامج كابدال بولاية جانت (El-Wahat Journal for Research and Studies, 2025)
The current study deals with the relationship between participatory democracy and local development by involving Kabdal program as a joint program between the European Union, the United Nations Development Program (UNDP) and the Algerian Ministry of Interior. It is a pioneering experiment aimed at achieving a model participatory approach targeting 10 municipalities, in an attempt to achieve results that contribute to building the self-capacities of these municipalities (Djanet municipality as a model).The program aims to embody participatory democracy at the local level and to involve community activities by forming them within Kabdal program. It also enhances the mobility of civil society and contributes to achieving local development in TasliNajer regionKey words: Participatory democracy, local development, Kabdal program, Djanet, local associations.